Survival Status and Predictors of Mortality Among Women with Uterine Rupture at Public Hospitals of Eastern Ethiopia. Semi-Parametric Survival Analysis - Alemu A; Yadeta E; Deressa A; Debella A; Birhanu A; Heluf H; Mohammed A; Ahmed F; Beyene A; Getachew T; Eyeberu A (International Journal of Women's Health, 2023)
Addisu Alemu,1 Elias Yadeta,2 Alemayehu Deressa,1 Adera Debella,2 Abdi Birhanu,3 Helina Heluf,2 Ahmed Mohammed,3 Fila Ahmed,1 Andinet Beyene,3 Tamirat Getachew,2 Addis Eyeberu2 1School of Public Health, College of Health and Medical Sciences, Haramaya University, Harar, Ethiopia; 2School of Nursing and Midwifery, College of Health and Medical Sciences, Haramaya University, Harar, Ethiopia; 3School of Medicine, College of Health and Medical Sciences, Haramaya University, Harar, EthiopiaCorrespondence: Addis Eyeberu, School of Nursing and Midwifery, Haramaya University, 138, Dire Dawa, Harar, Ethiopia, Tel +251910005436, Email addiseyeberu@gmail.comBackground: Uterine rupture is the most dangerous complication of labor and contributes to high maternal mortality. Despite efforts to improve basic and comprehensive emergency obstetric treatment, women continue to suffer from disastrous maternal outcomes.Purpose: This study aimed to assess the survival status and predictors of mortality among women with uterine rupture at public hospitals in the Harari Region, Eastern Ethiopia.Patients and Methods: We conducted a retrospective cohort study among women with uterine rupture in public hospitals in Eastern Ethiopia. All women with uterine rupture were followed for 11 years retrospectively. Statistical analysis was conducted with STATA version 14.2. Kaplan–Meier curves together with a Log rank test were used to estimate the survival time and show the presence of differences among groups. Cox Proportion Hazard (CPH) model was used to determine the association between independent variables and survival status.Results: There were 57,006 deliveries in the study period. We found that 10.5% (95% CI: 6.8– 15.7) of women with uterine rupture have died. The median recovery and death time for women with uterine rupture were 8 and 3 days with interquartile range (IQR) of 7– 11 days and 2– 5 days, respectively. Antenatal care follow-up (AHR: 4.2, 95% CI: 1.8– 9.79), education status (AHR: 0.11; 95% CI: 0.02– 0.85), visiting health center (AHR: 4.89; 95% CI: 1.05– 22.88), and admission time (AHR: 4.4; 95% CI: 1.89– 10.18) were the predictors of survival status of women with uterine rupture.Conclusion: One out of ten study participants died due to uterine rupture. Factors including not having ANC follow-up, visiting health centers for treatment, and being admitted during the night time were predictors. Thus, a great emphasis has to be given to the prevention of uterine rupture and the linkage within health institutions has to be smooth to improve the survival of patients with uterine rupture with the help of different professionals, health institutions, health bureaus, and policymakers.Keywords: emergency obstetrics, uterine rupture, predictors, mortality, Ethiopia